Pengaruh Disiplin Kerja dan Loyalitas Kerja Terhadap Kinerja Pegawai KPU Kota Batu - Vivin Syafiah; Budi Wahono; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to describe and determine partially and simultaneously the effect of work discipline and work loyalty on employee performance at KPU Batu City. Respondents in this study were employees of the KPU Batu City. The population of this study amounted to 35 people who were selected as a whole. Using saturated sampling. This type of research uses descriptive quantitative.Data analysis was performed using the SPSS 26 program. The results showed that the work discipline variable had no significant effect on employee performance. While the variable of work loyalty has a significant effect on employee performance. Simultaneously there is the influence of work discipline and work loyalty variables have a significant effect on employee performance at the Batu City KPU. Keywords: Work Discipline, Work Loyalty, Performance